Zasoby mebli w miejskich i wiejskich gospodarstwach domowych jako determinanta popytu - Garczarczyk, Józef (Wydział Prawa i Administracji UAM, 1972)
The author of this article describes the magnitude and structure of furniture resources in urban and rural households. Inquiry materials were a basis of this study. The analysis was made by assortment groups and not by separate assortments. A comparison between the magnitude and the structure of furniture resources in one household was drawn. Then the quantity of furniture per person, per one square meter of the surface of the dwellings and per one room was presented. The magnitude of the resources was also presented in the form of value by means of prices for the year 1970. The changing tendency in the field of structure of the resources was illustrated by means of a comparison to the data for the year 1962. The structure of the resources was also described by the period of use and the technical condition of the furniture. In the last place the origin of the furniture and the way of financing their purchase were presented.
Furniture Resources in Urban and Rural Households as Determinants of Demand